Now Davos draws the scholars, too - Abd Razak, Dzulkifli (2008)
MENTION Davos and one is likely to associate it with the prestigious World Economic Forum (WEF), the annual meeting of global political and business elite. The recent WEF was held last month and it drew some 2,000 participants, our prime minister among them. It is said that twothirds of the world's wealth is controlled or held by the people who turn up for the Davos meeting. Situated in the eastern Swiss Alps, Davos in the early 1970s (before the WEF came to the fore) was known only to skiers and wellheeled holiday makers. Snuggled high in the Alps, Davos is almost inaccessible except via a twohour train ride from Zurich with one change midway at Landquart.